Study the Effect of Seeding Suspension Concentration of DD3R Particles on the Modified Surface of Α-Alumina Support for Preparing DD3R Zeolite Membrane with High Quality - Aynaz Meshkat; Mohammad Javad Vaezi; Ali Akbar Babaluo (Ital Publication, 2018)
In this study, seeding of DD3R particles as an important step in the synthesis of DD3R membrane with secondary growth method was investigated. Dip-coating method is used for seeding of DD3R particles on the modified surface of α-alumina supports. 0.1, 0.2 and 0.3 wt% aqueous suspensions of the DD3R seeds were prepared and each support was coated three times with dipping time of 240 s. Scanning electron microscopy (SEM) analysis was used for the investigation of the quality of seed layer formed on the support. It is shown that the uniform layer of seeds was formed with 0.2 wt% seed suspension concentration. DD3R zeolite membrane was synthesized via hydrothermal method on the support seeded with 0.2 wt% seed suspension concentration. The X-ray diffraction and SEM analysis confirmed the synthesis of uniform DD3R zeolite membrane layer on the support which can be due to the uniform distribution of the DD3R seeds. Single gas permeation tests of N2, CO2 and CH4 were carried out, so that good perm-selectivity for gas mixtures was observed.